Effectiveness of staff training courses provided by Lembaga Kemajuan Ikan Malaysia / Nani Suriani Azmi - Azmi, Nani Suriani (Faculty of Business and Management, 2009)
The purpose of this research was to enhance our understanding on the dimension of the satisfaction of the employee about the training that the organization provided. The four model of independent variable that influences the effectiveness of the training provided there are facility, trainer, price and variety of training. The result was showing how the four dimensions will able to influence the effectiveness of the training in Lembaga Kemajuan Ikan Malaysia. The finding showed that the Lembaga Kemajuan Ikan was achieved and it means the training provided was effective. In this study, I used interview and questionnaire technique for a data collection. From the questionnaire I can conclude that almost all the staff was satisfied with the training provided by the LKIM. From the Statistical Package for Social Science (SPSS). We can look the clear finding and result is observed.